2017
DOI: 10.1186/s12891-017-1824-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for diffused-type giant cell tumor (pigmented villonodular synovitis) about the ankle joint

Abstract: BackgroundDiffused-type giant cell tumor(Dt-GCT) is a rare, aggressive disorder of the joint synovium, bursa and tendon sheaths. Osseous erosions and subchondral cysts may develop as the result of synovium infiltration in Dt-GCT. We present a retrospective study of a series of patients who are diagnosed with Dt-GCT about the ankle joint, there clinical outcome is evaluated in this study.Material and methodFifteen patients with radiologically and histologically confirmed Dt-GCT about the ankle joint were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In clinical work, GCTTS needs to be differentiated from lipoma, tendon cyst, epidermal cyst, sebaceous cyst, cyst calcification, hemangioma, osteochondroma, gout nodules, rheumatic nodules, tendon tuberculosis, tendon fibroma, and other rare diseases. 37,38 Physicians frequently observe the characteristics of related diseases and have rich clinical diagnosis experience, so the differential diagnosis of related diseases is not difficult to make. When a painless, sessile and relatively tough mass occurs on the hand of a female patient, GCTTS should be highly suspected.…”
Section: Clinical Differential Diagnosismentioning
confidence: 99%
“…In clinical work, GCTTS needs to be differentiated from lipoma, tendon cyst, epidermal cyst, sebaceous cyst, cyst calcification, hemangioma, osteochondroma, gout nodules, rheumatic nodules, tendon tuberculosis, tendon fibroma, and other rare diseases. 37,38 Physicians frequently observe the characteristics of related diseases and have rich clinical diagnosis experience, so the differential diagnosis of related diseases is not difficult to make. When a painless, sessile and relatively tough mass occurs on the hand of a female patient, GCTTS should be highly suspected.…”
Section: Clinical Differential Diagnosismentioning
confidence: 99%
“…Studies have shown that complete surgical resection is the gold standard for the treatment of GCT-TS (7), and open synoviectomy and bone grafting may be safe and effective surgery to save the ankle joint. Xingchen Li et al (8) believe that external fixation should be performed simultaneously to prevent pathological fracture in patients with severe bone and soft tissue damage. Ankle arthrodesis can be performed if necessary, and the patient will be transferred to the oncology department for further radiation therapy after the patient's condition stabilizes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent articles describe TSGCT in two sub-types: localized (L-) or diffuse (D-) TSGCT. L-TSGCT is usually painless, has a tendency to cause impingement due to tumor mass whereas D-TSGCT, which is also known as pigmented villonodular synovitis, shows up with pain, swelling and more osteochondral destruction (8).…”
Section: Introductionmentioning
confidence: 99%